Unsettled : Water and Sanitation in Urban Settlement Communities of the Pacific - World Bank Group (World Bank, Washington, DC, 2015)
Urbanization is occurring rapidly in Melanesia at 3-4 percent per annum. Due to unaffordable land and housing in formal urban areas, new migrants settle on marginal land without formal legal titles (‘informal settlements’). These settlements are growing and new settlements are emerging within and on the outskirts of towns and cities across Melanesia, at a rate that outpaces efforts to serve them. Settlements in the Melanesian capitals of Suva, Port Vila, Honiara, and Port Moresby comprise 20 percent-45 percent of the city population and at current urbanization rates will be between 30 percent and 65 percent by 2023. Information about informal settlements is scarce. This report provides a rapid review of water and sanitation services in the informal settlements in and around the capital cities of Solomon Islands, Fiji, Vanuatu, and Papua New Guinea.